PENGARUH VARIASI UKURAN BUTIRAN FILLER SERBUK GERGAJI BATANG KELAPA TERHADAP SIFAT MEKANIK KOMPOSIT - Cliffer Fridolin Poyoh; Fentje Abdul Rauf; Romels Cresano Apelles Lumintang (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2013)
Coconut tree (cocos nucifera) is one plant that is widely grown in North Sulawesi many benefits of the overall crop. Since sawdust coconut trunks are not optimally its utilization as a filler for composite materials is studied. In addition to eco-friendly materials are easily obtainable.This study aims to determine the mechanical properties of the composites tested bending (ASTMD 6110) and impact (ASTMD 256-00) with grain variation using mesh 250, 180, and 90 using polyester resin matrix. Optimum impact Is obtained using 250 Mesh 60% volume fraction of resinFrom the data processing Bending test optimum bending moment obtained at 250 mesh resin volume fraction of 70%, and optimum bending stress obtained on 250 mesh 70% volume fraction. For optimum deflection on 250 mesh fraction 70% volume for optimum bending rigidity is at 250 mesh 60% volume fraction. Then it shows the variation of grain size, the volume fraction affects the value of the mechanical strength of the composite.Keywords: Impact, Bending, Composites, volume fraction, Fille